2017
DOI: 10.1089/zeb.2016.1415
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Zebrafish Anxiety-Like Behavior Using Conflict-Based Novelty Tests

Abstract: Modeling of stress and anxiety in adult zebrafish (Danio rerio) is increasingly utilized in neuroscience research and central nervous system (CNS) drug discovery. Representing the most commonly used zebrafish anxiety models, the novel tank test (NTT) focuses on zebrafish diving in response to potentially threatening stimuli, whereas the light-dark test (LDT) is based on fish scototaxis (innate preference for dark vs. bright areas). Here, we systematically evaluate the utility of these two tests, combining meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 122 publications
5
147
0
1
Order By: Relevance
“…Previous studies reported a variety of behavioral tests and models such as the open field test, shoaling test, and impoverished housing, among which the light-to-dark test, CPP, T-maze and BDT were the most popular experimental models for zebrafish behavioral studies (Stewart et al, 2012) (Kysil et al, 2017); investigated the comparative analyses of zebrafish anxiety-like behavior using a novel tank test (NTT) and light-dark test (LTD), and found that some NTT and CPP endpoints, and endocrine (cortisol) levels were closely related to anxiety. Our results are consistent with these investigations demonstrating that CPP, BDT, ERa and ERb were linked with anxiety-or autism-like diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a variety of behavioral tests and models such as the open field test, shoaling test, and impoverished housing, among which the light-to-dark test, CPP, T-maze and BDT were the most popular experimental models for zebrafish behavioral studies (Stewart et al, 2012) (Kysil et al, 2017); investigated the comparative analyses of zebrafish anxiety-like behavior using a novel tank test (NTT) and light-dark test (LTD), and found that some NTT and CPP endpoints, and endocrine (cortisol) levels were closely related to anxiety. Our results are consistent with these investigations demonstrating that CPP, BDT, ERa and ERb were linked with anxiety-or autism-like diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Two assays -the novel tank test (Egan et al, 2009) and the light/dark test (Maximino et al, 2010b) -are widely used in this regard, with good pharmacological validation and construct validity for both tests Kysil et al, 2017); in both cases, threat is merely potential, as no predator or partial predator stimuli are present. In the novel tank test, the novelty of the environment elicit bottom-dwelling (also termed a "diving" response) that is associated with erratic swimming and freezing, representing defensive behaviour in this assay (Egan et al, 2009).…”
Section: Monoaminergic Innervation In Teleostsmentioning
confidence: 99%
“…In the light/dark test, the preference for a black compartment over a white one, associated with risk assessment behaviours, erratic swimming, thigmotaxis, and freezing is interpreted as defensive behaviour (Maximino et al, 2010b). Moreover, a relationship between stress and behaviour in these tests is established, as both acute (Giacomini et al, 2016) and chronic (Chakravarty et al, 2013;Marcon et al, 2016) stress increases defensive behaviour in these assays, and exposure to the apparatuses induce cortisol levels (Kysil et al, 2017). A causal link between neuroendocrine and behavioural responses to stress has not been ascertained; since these are modulated by monoamines, these neurotransmitters could link both functions.…”
Section: Monoaminergic Innervation In Teleostsmentioning
confidence: 99%
“…Nonetheless, zebrafish is the most widely studied species when it comes to fear, anxiety, and stress (Jesuthasan & Mathuru, 2008;Maximino et al, 2010a;Kalueff et al, 2012;Gerlai, 2013). Two assays -the novel tank test (Egan et al, 2009) and the light/dark test (Maximino et al, 2010b) -are widely used in this species, with good pharmacological validation and construct validity for both tests Kysil et al, 2017). In the novel tank test, the novelty of the environment elicit bottom-dwelling (also termed a "diving" response) that is associated with erratic swimming and freezing, representing anxiety-like behavior in this assay (Egan et al, 2009).…”
Section: Monoaminergic Innervation In Teleostsmentioning
confidence: 99%
“…Moreover, a relationship between stress and behaviour in these tests is established, as both acute (Giacomini et al, 2016) and chronic (Chakravarty et al, 2013;Marcon et al, 2016) stress increases anxiety-like behaviour in these assays, and exposure to the apparatuses induce cortisol levels (Kysil et al, 2017). A causal link between neuroendocrine and behavioural responses to stress has not been ascertained; since these are modulated by monoamines, these upstream modulators could link both functions.…”
Section: Monoaminergic Innervation In Teleostsmentioning
confidence: 99%